REVIEW ON COMPREHENSIVE DESCRIPTION OF DEVELOPMENT AND ASSESSMENT OF CO-CRYSTAL DRUG DELIVERY SYSTEM - BIDHURI, NAVEEN; PADHI, SWARUPANJALI (International Journal of Applied Pharmaceutics, 2023)
Over the past few decades, co-crystal Drug Delivery System (DDS) has attracted interest due to their potential to increase the solubility, stability, and bioavailability of medications that aren't sufficiently soluble. In this study, we factualized to develop a co-crystal chemical delivery system utilizing an experimental model. We utilized caffeine and succinic acid as model chemicals and prepared co-crystals utilizing different methods, including solvent evaporation, grinding, and spray drying. The co-crystals have been characterized utilizing X-ray powder diffraction, Fourier-transform infrared spectroscopy, and differential scanning calorimetry. The solubility and dissolution rate of the co-crystals has been evaluated in simulated digestive and intestinal juices. The outcomes showed that when compared to co-crystals made utilizing the solvent evaporation and spray drying procedures, those organized utilizing the grinding approach exhibited the maximum solubility and dissolution rate. This study underlines the potential of co-crystals as a workable method for enhancing the administration of pharmaceuticals that are not adequately soluble and provides a helpful experimental paradigm for the development of co-crystal chemical delivery systems.